Uma estratégia para transição suave de microrredes sem diferença de fase e de tensão - ROCHA, Gabriel Silva (2022)
In this work, Microgrid transition methods between grid-connected and isolated modes are presented and a transition method based on existing strategies, such as the cross product, is proposed to minimize the disadvantages of the traditional ones. The basic concepts about Microgrids and the main difference of a Critical Mission Microgrid regarding the others types is defined. Control structures are depicted at the primary, phase estimation, synchronism and secondary control level. The main proposal of the work is a modified control structure based on the estimation of the angle of the phase difference between the grid and the Microgrid, and on the use of a synchronism unit to provide smooth transitions of the Grid-Forming Converter control modes with no difference of phase and voltage. During synchronization, the synchronism unit varies the phase angle respecting the maximum frequency variation limits predefined for the Microgrid. While, during islanding, the estimated angle compensates the internal reference of the converter in order to eliminate transients related to sudden changes in phase reference. In the results, comparisons are carried out with methods from the literature and it was possible to prove that with the correct phase and voltage compensations, it is possible to practically eliminate the transients in the Microgrid voltage due to the switching of the control modes of the Grid-Forming Converter and the transition of the Microgrid operating mode.